2008
DOI: 10.1016/j.febslet.2008.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin‐mediated deacetylation pathway stabilizes Werner syndrome protein

Abstract: Caloric restriction (CR) is known to promote longevity in various species. Sirtuin-mediated deacetylation has been shown to be related to the promotion of longevity in some species. Here, we show that CR of rats led to an increase in the level of Werner syndrome protein (WRN), a recognized DNA repair protein. In addition, CR simultaneously increased the level of SIRT1, a mammalian sirtuin. In HEK293T cells, sirtuin inhibitors decreased the WRN level, and this effect was suppressed by proteasomal inhibitors. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…WRN, a nuclear protein mutated in WS, plays multiple roles in DNA metabolism including DNA replication, repair, and telomere maintenance [28]. In rats, calorie restriction-induced Sirt1 upregulation stabilizes and increases WRN in the liver [10]; however, there has been no previous study of the changes in WRN expression induced in ARF kidneys. In the present study, we first showed that WRN protein production is induced by 6 h after CDDP administration, after which the level remains high until at least 14 days later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WRN, a nuclear protein mutated in WS, plays multiple roles in DNA metabolism including DNA replication, repair, and telomere maintenance [28]. In rats, calorie restriction-induced Sirt1 upregulation stabilizes and increases WRN in the liver [10]; however, there has been no previous study of the changes in WRN expression induced in ARF kidneys. In the present study, we first showed that WRN protein production is induced by 6 h after CDDP administration, after which the level remains high until at least 14 days later.…”
Section: Discussionmentioning
confidence: 99%
“…We first examined the association between histone H3 deacetylation and changes in HDAC3 (the Rdp-related class I), HDAC5 (the Hsa2-related class II) and the mammalian homolog of silent information regulator 2 (Sir2), so-called Sirt1 (class III) for 14 days after CDDP injection. Since Sirt1 also deacetylates non-histone proteins including p53, DNA repair proteins, and several signaling factors [7][8][9], we next examined whether increased Sirt was related to acetylated p53 and Werner syndrome protein (WRN), a well recognized DNA repair protein which is a target for Sirt1 deacetylation [10,11], in CDDP-induced acute renal failure (ARF). We finally examined whether the transfection of Sirt1 mitigates the CDDP-induced cellar damage in human embryonic kidney (HEK) 293 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoblotting Immunoblotting was performed as described previously (Kahyo et al, 2008). Briefly, the protein concentration of the lysate was measured with a BCA protein assay kit (Thermo Scientific, Rockford, IL, USA).…”
Section: Antibodiesmentioning
confidence: 99%
“…In our experiments, independent treatments of human fibroblasts with HU, MMS, MMC, and cisplatin did not influence the total level of endogenous WRN protein but caused 2–4 fold increases in the levels of WRN protein that was acetylated. Although other reports have noted that WRN stability and abundance correlates to its acetylation status (Li et al 2010; Vaitiekunaite et al 2007; Kahyo et al 2008), the lack of changes in total WRN levels in our experiments may be due to shorter time frames for most of our experiments and/or our measurement of endogenous WRN instead of ectopically expressed WRN. Treatment with UV-C irradiation (20 or 40 J/m 2 ), however, had no significant effect on the levels of acetylated WRN.…”
Section: Discussionmentioning
confidence: 60%